Trends in ANPP response to temperature in wetland meadows across a subcontinental gradient in Patagonia - Irisarri, Jorge Gonzalo Nicolás (2022)
Due to ongoing global warming, seasonal patterns of aboveground net primary production (ANPP) may be altered by temperature trends. Of particular interest is the seasonal association between ANPP and temperature at the beginning of the growing season (the period encompassing minimum to maximum ANPP), where two contrasting mechanisms are in tension. On the one hand, the restrictions exerted by low temperatures in winter may be relaxed, increasing the slope of seasonal association between ANPP and temperature over the years. On the other hand, increases in temperature may increase water demand, reducing the slope over time. Across 543 wetland meadow areas in Patagonia, we estimated ANPP and obtained temperature records on a monthly basis from 2001 to 2019. The seasonal association between ANPP and temperature, tested through linear regression, was statistically significant in 96% of the cases (9921/10317 (543 wetland areas × 19 growing seasons)). The fitted linear models explained, on average, 84% of ANPP seasonal (June–December) variations. Through regression trees, we found out that the two tested mechanisms, the relaxation of temperature restriction and the increase in water demand, showed clear spatial patterns. The relaxation due to temperature increase took place at higher latitudes, but the water-limiting mechanism increased over mid-latitude areas.